Odpowiedzi

2010-03-19T18:18:44+01:00
tg α = 0,5
ctg α = 1/ tg α = 2
sin²α=sin²α /1=sin²α /(sin²α+cos²α)
dziele licznik i mianownik przez cos²α
sin²α=tg²α/(1+tg²α)
tzn
sinα=tgα/√(1+tg²α)

tak samo cos²α=cos²α/1=cos²α/(sin²α+cos²α)
dziele licznik i mianownik przez cos²α
cos²α=1/(1+tg²α)
cosα=1/√(1+tg²α)

LUB BEZ SZTUCZEK BO WYZEJ BYALA SZTUCZKA
sin²α+cos²α=1
sinα/cosα=tgα→sinα=tgα*cosα podstawiam

tg²α*cos²α+cos²α=1
cos²α[1+tg²α]=1
cos²α=1/(1+tg²α)
cosα=1/√(1+tg²α)

------ podobnie z sinusem

Pozdrawiam

Hans